FAKTOR-FAKTOR YANG MEMENGARUHI KNOWLEDGE SHARING DI ANTARA DOSEN (STUDI KASUS STIKOM UYELINDO DAN STIKOM ARTHA BUANA) - Semlinda Juszandri Bulan (Jurnal Sistem Informasi, 2016)
Knowledge sharing in an organization is a very important thing, one of the impact of these activities is to improve the performance of the organization. In academic sector, effective knowledge sharing among lecturers can improve the performance of a university. The purpose of this research